2002
DOI: 10.1080/87567550209595878
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Televised Courses: Student Perceptions of Teaching Effectiveness, with Recommendations

Abstract: A study of student satisfaction levels in interactive televised courses (ITV) presents research that supports the view that students appear to be unable to separate their perceptions of the teacher's effectiveness from that of the technology and method of course delivery. When other variables are held constant, students rated the effectiveness of the professor's teaching lower when ITV was involved. The implications for professors and students are discussed, and suggestions are offered regarding effective use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…In addition, informal solicitation from e-mails and face-to-face contact, indicated most students in the treatment condition reported that they chose the communication medium not because of any mindfulness of how they learn best, or their learning style, but because of time management issues. This trend is consistent with Anderson and Kent's (2002) study on interactive televised courses that found students chose to take televised courses because of travel and time considerations. Furthermore, recent studies have found that most students are incapable of regulating their learning to optimize self-directed learning in online environments (Azevedo & Cromley, 2004;Kramarski & Mizrachi, 2006) because few of them are skilled at deploying vital self-regulatory processes and mechanisms such as effective cognitive and metacognitive strategies (e.g., Azevedo & Cromley, 2004;Hadwin & Winn, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, informal solicitation from e-mails and face-to-face contact, indicated most students in the treatment condition reported that they chose the communication medium not because of any mindfulness of how they learn best, or their learning style, but because of time management issues. This trend is consistent with Anderson and Kent's (2002) study on interactive televised courses that found students chose to take televised courses because of travel and time considerations. Furthermore, recent studies have found that most students are incapable of regulating their learning to optimize self-directed learning in online environments (Azevedo & Cromley, 2004;Kramarski & Mizrachi, 2006) because few of them are skilled at deploying vital self-regulatory processes and mechanisms such as effective cognitive and metacognitive strategies (e.g., Azevedo & Cromley, 2004;Hadwin & Winn, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…This is underpinned by inquiry‐based learning, which is widely recognised as an effective approach for fostering critical thinking (Evangelisto, 2021; Fuad et al., 2017; Soneral & Wyse, 2017; Wahyudi et al., 2019; Zandvakili et al., 2019). Inquiry‐based approaches employ a student‐centred process which helps them to develop their own conceptual knowledge and frameworks (Anderson et al., 2013). Within these approaches, there is an emphasis on authentic problem‐solving within a connected and collaborative learning environment (Ku et al., 2014).…”
Section: Discussionmentioning
confidence: 99%